P‐6: 4‐side Micro Border 8k4k LCD with Oxide‐TFT Gate Driver Embedded Array. Issue 1 (25th September 2020) - Na, ManHong; Tung, Che-Wei; Lin, YuZuo; Lin, Wei-Li; Chen, Center
Abstract : We have realized the 4‐side micro (0.9x/0.9x/0.9x/0.9x mm) border 8k4k 120Hz LCD with Oxide thin‐film transistor (TFT) for the first time. Most of narrow border prototypes in past was 3‐side with 2‐COF process for both gate and data driving, but now, we have been developing the most cost effective 4‐side micro border LCD with only data COF. As core technology, 1G1D pixel driving and GDCIAA (Gate Driver Circuit in Active Area) with oxide TFT backplane are incorporated without any additional investment of module assembly. In practical point of view, this technology can render about 70% reduction of D‐IC cost and additional value up as a form factor of premium product compare to a‐Si TFT based LCD. Moreover, simplified 1G1D bus line structure can contribute to production yield improvement. In this report, we present the most valuable 8k4k LCD product with the latest AUOs Oxide TFT backplane technology.